STATEGIKEPALA SEKSI PENDIDIKAN MADRASAH DALAM MENINGKATKAN MUTU LAYANAN PENDIDIKAN ISLAM DI KANTOR KEMENTRIAN AGAMA KABUPATEN KARAWANG - Setya Darma, Adrian; Taufik BK, Muhamad; Saprialman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the leadership strategies of the Head of the Madrasah Education Section in improving the quality of Islamic education services at the Ministry of Religious Affairs Office of Karawang Regency. Specifically, it examines the strategies implemented, the factors influencing their implementation, and their contribution to service quality improvement. This study employed a qualitative approach with a case study method. Data were collected through in-depth interviews, observations, and documentation involving the Head of the Madrasah Education Section and related stakeholders. Data were analyzed using data reduction, data display, and conclusion drawing, while credibility was ensured through source and technique triangulation. The findings reveal that leadership strategies were implemented through strengthened coordination with madrasah principals and stakeholders, continuous coaching and mentoring, regular monitoring and evaluation, competency development for educators and education personnel, and the use of information technology to support educational administration. Their implementation was supported by leadership competence, organizational commitment, and stakeholder collaboration, although constrained by limited resources, the large number of supervised madrasahs, and evolving education policies. These strategies contributed to improved coordination, more effective guidance, greater service responsiveness, and enhanced quality of Islamic education services. This study contributes to the field of Islamic Education Management by highlighting the importance of educational bureaucratic leadership in improving the quality of Islamic education services.